Digital Innovation Capability and Customer Value Co-Creation on New Product Performance with Digital Transformation Maturity as a Moderating Variable in Trading Companies in Indonesia - Fransisca, Luciana; Renaldo, Nicholas; Chandra, Teddy; Augustine, Yvonne; Musa, Sulaiman (Luxury: Landscape of Business Administration, 2025)
This study investigates how digital innovation capability and customer value co-creation influence the performance of new products, with digital transformation maturity serving as a moderating variable. The novelty of this research is the development of indicators, especially on the variable of co-creation of customer value. This quantitative research will collect data using a structured questionnaire, employing a 6-point Likert scale. The data will be analyzed using Structural Equation Modeling (SEM) to examine the relationships between variables and test the proposed hypotheses. The sample size will be a minimum of 155 respondents. The findings confirm that Digital Innovation Capability and Customer Value Co-Creation positively influence New Product Performance. However, Digital Transformation Maturity does not strengthen these relationships, suggesting that high levels of digital maturity may introduce rigidity, reduce human-led innovation, and shift focus toward efficiency rather than customer engagement. Future studies should compare different industries (manufacturing, services, technology) to explore whether digital transformation maturity has varying effects on product performance. Future research should track the long-term impact of digital innovation and customer co-creation on new product success over multiple years.